2011
DOI: 10.1007/s11581-011-0522-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity and chemical stability of perovskite-type BaCe0.8-x Ti x Y0.2O3-δ

Abstract: Here we report the synthesis, chemical stability, and electrical conductivity of Ti-doped perovskite-type BaCe 0.8-x Ti x Y 0.2 O 3-δ (x=0.05, 0.1, 0.2, and 0.3; BCTY). Samples were synthesized by conventional solid state (ceramic) reaction from corresponding metal salts and oxides at elevated temperature of 1,300-1,500°C in air. The powder X-ray diffraction confirmed the formation of a simple cubic perovskite-type structure with a lattice constant of a=4.374(1), 4.377(1), and 4.332(1) Å for x=0.05, 0.1, and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
(88 reference statements)
1
12
1
Order By: Relevance
“…Incorporation of zirconium into the doped barium cerate results in improving the chemical and mechanical stability [20,21] but leads to decreasing of conductivity especially due to poor sinterability of barium zirconate. Similar results were obtained by doping BaCeO 3 with yttrium and titanium [22,23].…”
Section: Introductionsupporting
confidence: 82%
“…Incorporation of zirconium into the doped barium cerate results in improving the chemical and mechanical stability [20,21] but leads to decreasing of conductivity especially due to poor sinterability of barium zirconate. Similar results were obtained by doping BaCeO 3 with yttrium and titanium [22,23].…”
Section: Introductionsupporting
confidence: 82%
“…Materials of the same system with a wider yttrium concentration changes were studied by Talimi and Thangadurai [36]. Complex oxides were obtained by the aid of a solid phase synthesis at 1450°С for 24 h. Despite the fact that maximum synthesis temperature was the same as in the previous work [32], the BaCe 0.8-х Ti х Y 0.2 O 3-δ (х=0.05, 0.1, 0.2) materials crystallize into a cubic structure with unit cell parameters of 4.374, 4.377 and 4.332Å, respectively.…”
Section: Ti-containing Materialsmentioning
confidence: 99%
“…In addition, the conductivity in humid hydrogen is slightly lower than that in air. Based on the level of activation energy, calculated using conductivity dependencies on temperature, Talimi et al [36] concluded that the materials behaved like ionic-hole conductors in air and like co-ionic ones in humid hydrogen atmosphere. The influence of yttrium on the properties of barium cerate, containing small amount of titanium, was studied by Pasierb et al [37].…”
Section: Ti-containing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermodynamic data suggest that barium cerate is an unstable phase in the wide temperature range [11][12][13]. The ΔG of the reaction of barium carbonate formation (Eq.…”
Section: Introductionmentioning
confidence: 99%